Treatment of Hypertension by General Practitioners and Antihypertensive Drugs Expenditure in an Urban Environment - Bergman-Marković, Biserka (Array, 2009)
Abstract: Aim of our study was to determine the treatment habits of hypertension by general practitioners (GPs) as well as the monthly costs of prescribed antihypertensive drugs and their share in the total prescription drug expenditure approved by the Croatian Institute for Health Insurance (CIHI), the compulsory health insurance system. The study was performed in six GPs offices in Zagreb, serving 8,866 patients, in December 2005. The monthly costs of antihypertensive drugs prescribed by the GPs was obtained by summarizing the prices of all antihypertensive drugs prescribed in one month and then comparing the sum with total monthly prescription drug expenditure approved by the CIHI. The type and dosage of prescribed antihypertensive drugs were also analyzed. Hypertension was diagnosed in 2,342 (26.4%) patients. The monthly costs of prescribed antihypertensive drugs accounted for 52.33% of the total amount approved for medications by the CIHI. 945 (40.0%) hypertensive patients were taking antihypertensive monotherapy. The most frequently prescribed drugs as monotherapy were ACE inhibitors (38.3%), calcium-channel blockers (26.7%), b blockers (18.6%), and diuretics (10.3%). a antagonists (3.6%). Angiotensin receptor blockers (2.5%) were rarely prescribed. As combination therapy, ACE inhibitors and diuretics (30.4%) were most frequently used. More than 50% of the funds allocated to GPs for medications were spent for the treatment of only one disease. The most used antihypertensive drugs were ACE inhibitors